(untitled) (Polish Yearbook of International Law, 2021)
Among UN human rights treaty bodies that have the competence to examine inter-state communications, only the Committee on the Elimination of Racial Discrimination (CERD) has had the possibility to develop its case law in this regard (as of 2020). One of these cases – submitted by the State of Palestine against Israel – resulted in a controversy arising from the respondent state’s declaration excluding any treaty relations between Palestine and Israel, the latter considering the former “a non-recognized entity.” The present paper analyses the CERD’s decision of 12 December 2019 in which the Committee found that it had jurisdiction to hear the inter-state communication. The author argues that while invocation of the “special character” of human rights obligations constitutes a powerful argument in judicial discourse, this should not lead to (re)opening debates on self-contained regimes and alienating human rights treaties from the norms and principles of general international law. At the same time, there are also valid reasons to perceive the obligations enshrined in the ICERD as being of a specific and erga omnes character.